Labor contracting, farms, and wagework markets in grapes production of the Cuyo región, Argentina - Neiman, Guillermo (2016)
This article deals with the phenomenon of labor intermediation within the context of restructured crops associated with quality-based productive patterns. In these scenarios intermediation redefines its forms, takes more complex functions and modifies some of its main features. Specifically, labor intermediation is discussed for grapes crops grown under quality productive patterns (including grapes for the elaboration of wines as well as for fresh consumption) in the so called region of Cuyo in Argentina. The article primarily questions the relationship between labor intermediation and workforce mobilization and organization in those scenarios. The importance of this type of contract in a highly casual labor market where the labor intermediary not only hires workers but also organizes, supervises and exerts control of the labor process is highlighted. Besides, the influence of local labor markets conditions is underlined in order to understand labor intermediation in quality-based agriculture.